Penerapan Penghimpunan Dana Nasabah Pada Akad Wadi’ah Di BMT NU Cabang Blutoh Sumenep - Abdussakur Abdussakur; Kristiani Utami (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Wadi'ah in principle is to help the custodian, and the party entrusted with his position as a helping party. Therefore, the nature of wadi'ah is trust. In the book I'anatut Thalibin by Ad Dimyathy it is explained that wadi'ah is: